Pemanfaatan Instagram Dalam Pemasaran Produk Usaha Kecil Menengah Keripik Tempe Alkhalif Pada Masa Pandemi Covid-19 - Annisa Utami Wallad; Nurlaila Nurlaila (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2021)
This study aims to analyze the use of Instagram in the marketing of Alkhalif Tempe Chips small and medium business products during the Covid-19 pandemic. The method used in this research is a qualitative research with a descriptive approach. The informants in this study were the owners of Alkhalif Tempe Chips UKM. Data collection techniques used are observation, interview and documentation techniques. The techniques used in data analysis are data collection, data reduction, data presentation, and drawing conclusions. Triangulation is done to explain the validity of the data by using source triangulation. The results showed that the use of Instagram in product marketing for small and medium-sized businesses Alkhalif Tempe Chips included: (1) The use of Instagram by Alkhalif Tempe Chips SMEs in product marketing through Instagram features, namely, Upload photos and videos, Captions, comments, Likes, Instagram Stories, IGTV, Hasthagh, Direct Message; (2) The use of Instagram as a product marketing medium for Alkhalif Tempe Chips SMEs provides benefits in business development, namely being one of the strong drivers for SMEs to continue to develop their business; (3) The problems that occur in marketing Alkhalif Tempe Chips products through Instagram are in terms of managing Instagram media, namely the slow response of buyers because the owner himself manages Instagram. And also buyers who compare prices with other sellers; (4) The income of Alkhalif Tempe Chips UKM in marketing products through Instagram has increased sales by up to 40% with previous sales.